Dynamika relacji między organizacją i otoczeniem - perspektywa procesów związanych z wiedzą - Stańczyk-Hugiet, Ewa (Organization - environment dynamics - perspective of knowledge processes, 2006)
Presented paper is concern on organization - environment dynamics. This dynamics is viewed as relations between internal and external structure. Precisely this relations are analyzed as knowledge processes. Finally are shown empirical data based on importance and intensity of knowledge processes between internal and external structure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 163-169